Analysis of effective factors on planning of tourism development (Case study, Maku free zone) - Mohammadrahim Rahnama; Mahdi Abdolahzadeh (نشریه جغرافیا و برنامه‌ریزی, 2018)
In this research, factors influencing the advancement of local participation culture in tourism development planning in Maku free zone were evaluated.Research method used was descriptive – analytical and practical. The population studied in this research includes people living around Maku free zone with 183,453 persons, among whom 383 persons were chosen based on Cochrane formula. To gather data for the present study, questionnaire was used which is designed based on 38 questions (4 general questions, and 34 special questions); and to determine its validity and reliability, content validity and Cronbach''s alpha coefficient were used. Obtained alpha was 0.824. The Sample population was selected through simple random sampling, cluster sampling and Stratified sampling. To analyze the data, descriptive statistics and inferential statistics (methods such as regression and path analysis) were used. Based on the results obtained from path analysis and conceptual model test, empowerment of local communities resulted in the strengthening of local social capital, and high level of social capital leads to the increase in local participation culture in planning and development of tourism. Furthermore, comprehensive planning of tourism development provides legal framework for the strengthening of social capital and persuasion of investment in social capacity, and facilitates empowerment of local community.